Identification of GC-rich LAT genes in birds - Janusova, Sarka; Krchlikova, Veronika; Hron, Tomas; Elleder, Daniel; Stepanek, Ondrej (PloS one, 2023)
Linker for activation of T cells (LAT) plays a key role in T-cell antigenic signaling in mammals. Accordingly, LAT orthologues were identified in the majority of vertebrates. However, LAT orthologues were not identified in most birds. In this study, we show that LAT gene is present in genomes of multiple extant birds. It was not properly assembled previously because of its GC-rich content. LAT expression is enriched in lymphoid organs in chicken. The analysis of the coding sequences revealed a strong conservation of key signaling motifs in LAT between chicken and human. Overall, our data indicate that mammalian and avian LAT genes are functional homologues with a common role in T-cell signaling.
Keywords: genom; adaptorové proteiny signální transdukční; membránové proteiny; T-lymfocyty; T-Lymphocytes; Chickens; zvířata; Humans; Adaptor Proteins, Signal Transducing; Membrane Proteins; Genome; Mammals; savci; Phosphoproteins; kur domácí; lidé; fosfoproteiny; Animals